Development of a Method for the Quantitative Determination of Genisten for the Certification of a Certified Reference Material - A. A. Zhigalina; O. Yu. Strelova; A. N. Grebenyuk (Разработка и регистрация лекарственных средств, 2022)
Introduction. One of the priority directions in the development of modern pharmacy is the search for new highly effective pharmaceutical substances with a high spectrum of pharmacological action and low toxicity. As a result of studies conducted by a number of authors, positive results have been shown for the use of genistein for the prevention and treatment of cardiovascular diseases and osteoporosis in menopausal women. It exhibits hypocholesterolemic and antidiabetic effects, as well as radioprotective properties. A comparative evaluation of genistein from soybean seed cake [Glycine max (L.) Merr.] and synthesized by SPC "Pharmzashchita" and the department of chemical technology of medicinal substances, SPCPU was carried out. Studies of natural genistein by GC-MS showed the presence of an admixture of a related isoflavone, daidzein, in the sample. The synthesized genistein was assessed in terms of qualitative analysis.Aim. The aim of our study was to develop a method for the quantitative determination of genistein for its certification as a CRM.Materials and methods. The object of the study was 96 % genistein (abcr. Gute Chemie, Германия). Quantitative determination by non-aqueous titration was carried out on a laboratory pH meter F20 (METTLER TOLEDO, USA) in a reagent grade DMFA medium (JSC "EKOS-1", Russia). The HPLC study was carried out on an Agilent 1200 Series high-performance liquid chromatograph LC-20 Prominence (Shimadzu, Japan).Results and discussion. The method of non-aqueous titration in DMFA medium which recommended by the State Pharmacopoeia of the Russian Federation XIV edition, titrant 0.1 M sodium hydroxide solution, was used as the basis for the development of a method for the quantitative determination of genistein. The end point of the titration was set using thymol blue indicator. However, the difficulty in visual fixation by changing the color of the indicator was noted. It has been proposed to use a potentiometric end-point determination. For the quantitative determination of genistein in dietary supplements and drugs containing this substance a HPLC method was proposed.Conclusion. A method for non-aqueous titration of genistein with potentiometric end-point determination in DMFA medium has been developed. The integral curve is not very informative for a clear definition of the titration end point. It is recommended to use a differential curve. The validation evaluation of the obtained results showed that the method is trueness (RSD, % = 1.25), precision (RSD, % = 1.21) and intermediate precision (on the first day of RSD, % = 1.21, on the second day of RSD, % = 1.41).